Translating ecological narratives: A linguistics and cross-cultural analysis of ‘Laskar Pelangi’ from Indonesian to German - Lapasau, Merry; Hidayat, Ryan; Rafidah, Nik; Arjulayana, Arjulayana (BAHASTRA, 2026)
Translation studies face enduring challenges in conveying ecological themes across linguistic and cultural boundaries. This research explores how ecological dimensions in Andrea Hirata’s Laskar Pelangi (LP) are represented in its German translation, Die Regenbogentruppe (RBT). Grounded in Vinay and Darbelnet’s translation theory, the study examines key ecological elements -landscapes, flora, fauna, environmental degradation, and eco-cultural practices-and analyzes how translation strategies influence their portrayal. The research adopts a comparative and eco-critical approach, combining textual analysis with a focus on the sociocultural implications of translation choices. Findings reveal that procedures like equivalence, adaptation, borrowing, literal translation, and modulation predominantly align with target-language norms, reflecting a balance between cultural domestication and fidelity to the source text. This study not only sheds light on the translator's role in mediating ecological narratives but also contributes to discussions on how translated literature can foster cross-cultural ecological awareness. By emphasizing the interplay between translation strategies and ecological representation, this research underscores the potential of literary translation as a tool for global environmental advocacy, providing theoretical and practical insights for scholars and practitioners in translation studies and ecological linguistics. Pedagogically, the study highlights how translation practice and instruction can foster ecological literacy and global responsibility, encouraging learners to connect linguistic sensitivity with environmental ethics.